O perspectivă contrastivă asupra versiunilor latinești ale operei cantemiriene CURANUS - Florentina Nicolae (Revista de Istorie și Teorie Literară)
In this study we aim to analyze two Latin versions, entitled Curanus and De Curani etymologico nomine, of Dimitrie Cantemir’ The System or the Structure of the Muslim Religion, printed in Russian, in 1722. The first version is shorter, containing many cuts and marginal notes, some of which were inserted in the second version, enlarged and very close to the Russian variant. The contrastive analysis of the two Latin versions will mainly look at structural changes, perspective on bibliographic information, the importance of elements added to the second Latin version.